Analysis of Digital Transformation over Agile Delivery of Complex Project Management Including Cloud, AI, and Blockchain Technologies - Tiwari, Vipul (Digital Repository of Theses, 2025)
Digital transformation has radically remodeled the landscape of complex project management, particularly in Agile delivery frameworks. This research investigates the impact of Cloud Computing, Artificial Intelligence (AI), and Blockchain technologies on Agile methodologies used for management large-scale, high-complexity projects. By scrutinizing real-world applications, the study highlights how digital transformation develops Agile delivery through automation, real-time data handling, predictive analytics, and distributed security. The paper discovers key factors manipulating Agile success in digitally converted environments, including adaptive planning, continuous integration, and cross-functional collaboration. Additionally, it recognizes challenges such as scalability, data privacy concerns, and interoperability when combining these evolving technologies. By providing perceptions into best practices and strategic frameworks, this research intends to assist organizations in augmenting Agile methodologies for improved project effectiveness, risk alleviation, and innovation-driven growth. Keywords: Digital Transformation, Agile Project Management, Cloud Computing, Artificial Intelligence (AI), Blockchain Technology, Complex Project Delivery, Continuous Integration, Predictive Analytics, Automation in Agile, Risk Mitigation